2017
DOI: 10.1002/jcp.26247
|View full text |Cite
|
Sign up to set email alerts
|

The Shc protein RAI promotes an adaptive cell survival program in hypoxic neuroblastoma cells

Abstract: Neuroblastoma (NB) is a highly malignant pediatric solid tumor where a hypoxic signature correlates with unfavorable patient outcome. The hypoxia-inducible factor (HIF)-1α plays an important role in NB progression, contributing to cell proliferation and invasiveness. RAI belongs to the Shc family proteins, it is mainly neuron specific and protects against cerebral ischemia. RAI is also expressed in several NB cell lines, where it promotes cell survival. In this work, hypoxia differently affected cell survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Previous reports indicate that the adapter protein Rai positively controls the survival of neuroblastoma cells (Miyake et al, 2002; Miyake et al, 2005; Miyake, Ohira, Nakagawara, & Sakai, 2009) and that Rai plays a protective role against cerebral ischemia (Troglio et al, 2004). More interestingly, we have recently shown that Rai is relevant in protecting neuroblastoma cells against cell death induced by hypoxia by promoting HIF‐1α accumulation and HIF‐1α‐related signaling (Criscuoli et al, 2018). We report here that Rai promotes HIF‐1 accumulation also in hypoxic T cells, suggesting that Rai may be involved in the modulation of HIF‐1α expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports indicate that the adapter protein Rai positively controls the survival of neuroblastoma cells (Miyake et al, 2002; Miyake et al, 2005; Miyake, Ohira, Nakagawara, & Sakai, 2009) and that Rai plays a protective role against cerebral ischemia (Troglio et al, 2004). More interestingly, we have recently shown that Rai is relevant in protecting neuroblastoma cells against cell death induced by hypoxia by promoting HIF‐1α accumulation and HIF‐1α‐related signaling (Criscuoli et al, 2018). We report here that Rai promotes HIF‐1 accumulation also in hypoxic T cells, suggesting that Rai may be involved in the modulation of HIF‐1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that hypoxia induces T cell death through the activation of a proapoptotic program and the involvement of the p66Shc protein (Carraro et al, 2007;Naldini et al, 2010). More recently, we have reported that the expression of the Shc protein Rai protects neuroblastoma cells against cell death induced by hypoxia (Criscuoli et al, 2018). (Raman, Chen, & Cobb, 2007).…”
Section: Rai Protects T Cells Under Hypoxia By Activating Pro-survimentioning
confidence: 96%
See 1 more Smart Citation
“…Total RNA was extracted following manufacturer's instructions. Complementary DNA was synthesized using iScript™cDNA Synthesis Kit (Bio-Rad Laboratories) and reverse transcription quantitative polymerase chain reaction was performed using SsoAdvanced™ Universal SYBR ® Green Supermix (Bio-Rad Laboratories), using an iQ™ 5 Muticolor Real-Time PCR Detection System (Bio-Rad Laboratories) as previously described (Criscuoli et al, 2017). Primers for SMO, CAXII, and β-actin were designed with Primer BLAST program (NCBI, 2016).…”
Section: Reverse Transcription Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…7 ShcA plays a role in insulin signaling, stress resistance and energy metabolism. 8 ShcA exists in three splicing isoforms: p46shc, p52shc, and p66shc 9 . The p52 and p46 forms of ShcA are able to activate the Ras and MAP kinase pathway.…”
Section: Introductionmentioning
confidence: 99%